Habitat protection of important medicinal plants by screening and cultivation of promising germplasm - GULERIA, VIPAN; THAKUR, JITENDER (The Indian Journal of Agricultural Sciences, 2026)
The conservation, habitat protection, cultivation, optimizing yield parameters for increased productivity can be the long term strategy of conserving and protecting the important high value drug plants such as Valeriana jatamansi, Picrorhiza kurrooa and Aconitum heterophylum, which were once upon found in the abundance in the in the temperate region of western Himalayas in the Pir -panjal ranges of the Chamba of Himachal Pradesh. The study was conducted in the area of 32° 10// to 33°13// N latitude and 75°45// E to 77°33// E longitude limits ranging from the altitudes of 1200 to 4398 above msl. The wide area of availability of these species was surveyed and germplasm was collected. The highest survival percentage of Valeriana jatamansi species ranged from 80 to 95 percent it was followed by the survival percent of Picrorhiza karrooa species which ranged from 71.33 %-80.00 %. However, the survival percent Aconitum heterophylum ranged from 67-78 percent.